Strategi Pengembangan Potensi Wisata Bahari Pulau Tunda, Kecamatan Tirtayasa, Kabupaten Serang, Provinsi Banten - Bangga Prameswara; Ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2019)
The study aims to determine Development Strategy the potency of the Tunda Island as a tourist attraction in the Serang Regency, Banten Province. How the development of appropriate strategy to overcome obstacles in the development of Tunda Island Coast region as a Marine Tourism attraction in Serang Regency, Banten Province. This study was conducted to determine the Tunda Island as a marine tourism destination Serang Regency were reviewed by using SWOT analysis. This study uses quialitative research methods with data collection techniques such as interviews, observation, and documentation studies. The results of the research carried out that Pulau Tunda as a marine tourism attraction in Serang Regency has the power in the form of underwater natural potential that is different from other islands in Serang Regency, besides Tunda Island has a considerable opportunity for increasing tourism needs and locations that tend to strategic. However, Pulau Tunda has weaknesses in the quality of human resources as well as low tourism support facilities and garbage that has not been managed properly. Meanwhile the threat faced by Tunda Island is currently the operation of sand miners and the lack of attention from the local government. Keywords: Development Strategy, Tunda Island, Marine Tourism